Protocols and documents approved by the Educational Inspection of Andalusia - Pérez Aguilar, José Francisco (Avances en Supervisión Educativa, 2017)
At present, the different professional fields elaborate protocols whose main purposes are usually focused on developing their techniques, saving time and facilitating their specialized work. These protocols include methods to be developed, instruments to be applied and guidelines to be followed in order to achieve objectives through approved procedures that respond to the demands and specific situations requested. The educational inspection is not alien to this reality and, progressively, elaborates its protocols and approved documents; Likewise, it updates and publishes them so that the actions of the inspectors can be carried out with legal certainty and transparency so that their motives, results and assessment are known. In addition to the above, the protocols enable efficient and efficient development, as well as a response in time and form with savings of effort. In the present article, a brief theoretical framework will be tested to situate the object of the same, analyze the planning and development of the inspection work and the evidences gathered in the action plans, related to the protocols and approved documents of the educational inspection of Andalusia.